OPTICAL PROPERTIES OF THIN Cu FILMS AS A FUNCTION OF SUBSTRATE TEMPERATURE (Journal of Sciences, Islamic Republic of Iran)
Copper films (250 nm) deposited on glass substrates, at different substrate temperatures. Their optical properties were measured by ellipsometery (single wavelength of 589.3 nm) and spectrophotometery in the spectral range of 200–2600 nm. Kramers Kronig method was used for the analysis of the reflectivity curves of Cu films to obtain the optical constants of the films, while ellipsometery measurement was carried out as an independent method. The influence of substrate temperature on the microstructure of thin metallic films [Structure Zone Model (SZM)] is well established. The Effective Medium Approximation (EMA) analysis was used to establish the relationship between the SZM and EMA predictions. Good agreements between SZM as a function of substrate temperature and the values of volume fraction of voids obtained from EMA analysis, are obtained; by increasing the substrate temperature the separation of the metallic grains decreases hence the volume fraction of voids decreases and denser films are formed. The unusual (anomalous) behavior of the void fraction as a function of wavelength for different substrate temperatures, in certain wavelength region is explained to be due to the roughness value of the film surface. This value corresponds to this wavelength region scattering from the surface roughness. This phenomenon may be used as a technique for surface roughness measurement.